Reflecting on the intersectional aspects of the Durban Conference (2001): two decades of developments in the context of racial relations in Brazil - Lessa, Luciana Falcão (2025)
The Brazilian Black Women’s Movement played a crucial role In the preparation and construction of the III World Conference Against Racism, Racial Discrimination, Xenophobia, and Related Intolerances, held In 2001 In South Africa. At the Conference, the Brazilian State, pressured by Black movements, acknowledged the central role of racism In perpetuating Inequalities and committed to combating it through affirmative actions. Following the Conference, the debate on university quotas gained prominence In Brazil, and education, a historic demand of the Unified Black Movement (MNU), overshadowed the leadership of Black women. This article aims to explore the Intersectional aspects of the Durban Conference, repositioning Black women as central figures and examining its impacts In Brazil through public policies that address both gender and race. Such policies are crucial for addressing structural Inequalities In society. The analysis of Black feminist approaches and the concept of Intersectionality allows us to recover and appreciate the contributions of Brazilian Black activists In fighting racism and sexism.